Effectiveness of repair method using hybrid fiber reinforced polymer fabric on concrete-filled double skin steel tubular columns exposed to fire - Mohd Zuki, Sharifah Salwa; Shahidan, Shahiron; Choong, Kok Keong; Jayaprakash, J. (Construction Research Institute of Malaysia (CREAM), 2018)
Concrete-filled double skin steel tubular (CFDST) columns were often used in outdoor construction where fire is not a main concern. Therefore, this series of research deals with behaviour of CFDST columns after fire exposure, residual strength and method of repairing fire-damaged columns. This particular paper focused on the effectiveness of Hybrid Fiber Reinforced Polymer (FRP) repairing method. Total of 42 specimens were casted and 36 of the specimens were exposed to ASTM E-119 until the temperature of 600˚C. After that, the temperature was kept constant for 60 and 90 minutes. Out of 36 specimens that were exposed to fire, 24 of the specimens were repaired with FRP using hand lay-up method. All of the specimens (control, heated unrepaired and heated repaired) were subjected to concentric axial loading. It was found that by using Hybrid FRP, the ultimate strength at failure of repaired specimens greatly increased when compared to fire-damaged specimens to the extent of exceeding the control specimens. In addition, FRP is also effectively confined thinner outer steel tube than thicker outer steel tube. However, the effectiveness of Hybrid FRP repair method depends on several factor such as thickness of outer steel tube and maximum exposure time.